JURIDICAL ANALYSIS OF THE EUROPEAN UNION’S ANTI-DUMPING MEASURES ON BIODIESEL IMPORTS FROM INDONESIA: A CASE STUDY OF WORLD TRADE ORGANIZATION (WTO) DISPUTE SETTLEMENT BODY DECISION NO. DS480 - Safiya Dwi Aprilia; Diva Pitaloka (Mataram Journal of International Law, 2026)
This study provides a juridical analysis of the anti-dumping duties imposed by the European Union on biodiesel imports from Indonesia, focusing on the case study of World Trade Organization (WTO) Dispute Settlement Body (DSB) Decision No. DS480. The research questions addressed in this study are: what legal measures can Indonesia take to implement the DSB decision, and how can the implementation of such decision protect the national biodiesel industry from unfair trade practices? This study employs a qualitative normative juridical method, using official WTO documents, international agreements, and relevant regulations as primary legal materials. The findings show that the WTO Panel ruled that the European Union’s anti-dumping measures were inconsistent with the Anti-Dumping Agreement and the General Agreement on Tariffs and Trade 1994, particularly in relation to the determination of production costs, the calculation of dumping margins, and the evidence of injury to the domestic industry. This decision requires the European Union to adjust its measures in accordance with the applicable principles of international trade law and strengthens Indonesia’s position in multilateral forums.